2022
DOI: 10.3171/2021.8.spine21651
|View full text |Cite
|
Sign up to set email alerts
|

Long-term functional outcome of surgical treatment for degenerative cervical myelopathy

Abstract: OBJECTIVE Degenerative cervical myelopathy (DCM) is a major global cause of spinal cord dysfunction. Surgical treatment is considered a safe and effective way to improve functional outcome, although information about long-term functional outcome remains scarce despite increasing longevity. The objective of this study was to describe functional outcome 10 years after surgery for DCM. METHODS A prospective observational cohort study was undertaken in a university-affiliated neurosurgery department. All patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…This study demonstrated satisfactory results with a significant increase in mean modified Japanese Orthopedic Association (mJOA) score from baseline to a 2-year follow-up, and the results were unchanged at a 10-year follow-up. 9 A recent retrospective study with 195 patients with a mean follow-up of 6.3 years demonstrated neurological improvement in 89% at 5 years and 76% at 10 years. No PROMs were reported in the long-term follow-up in this study.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This study demonstrated satisfactory results with a significant increase in mean modified Japanese Orthopedic Association (mJOA) score from baseline to a 2-year follow-up, and the results were unchanged at a 10-year follow-up. 9 A recent retrospective study with 195 patients with a mean follow-up of 6.3 years demonstrated neurological improvement in 89% at 5 years and 76% at 10 years. No PROMs were reported in the long-term follow-up in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated satisfactory results with a significant increase in mean modified Japanese Orthopedic Association (mJOA) score from baseline to a 2-year follow-up, and the results were unchanged at a 10-year follow-up. 9…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations